STUDY ON THE EFFECT OF PRESSURE AND TEMPERATURE ON HYDRODEOXYGENATION OF GUAIACOL USING BATCH REACTOR WITH NI/AL-MCM-41 CATALYST - CHEE MUN, MAK (IRC, 2017)
Depletion of fossil fuel reserves has urged active researching effort in search of alternative source of energy. Biomass energy has raised to be one of the most promising solution to replacing conventional liquid fuel and fossil fuel energy. Bio-oils, an attractive energy carrier can be produced from a thermal conversion process called fast pyrolysis. However, bio-oil produced is mainly composed of lignin-derived phenolic compounds which lead to undesired properties such as acidity, thermal instability, low heating value and high viscosity. These undesired properties make the application of biomass energy challenging in practical field. A method to upgrade bio-oil is by removing the oxygen content with a catalytic hydrodeoxygenation reaction (HDO). In this study, guaiacol was used as the model compound to investigate the effect of temperature and pressure on hydrodeoxygenation reaction. Experiment was performed in a high-pressure batch reactor, autoclave with Ni/Al-MCM-41 as catalyst. The result obtained shows that the main products are catechol, di-methoxybenzene and phenol. Significant formation of methane was discovered in 350⁰C reaction. Selectivity of reaction towards HDO was higher at 250⁰C compared to higher temperature, 300⁰C and 350⁰C. However, conversion of guaiacol increases as the reaction temperature increases. Thus, highest yield of deoxygenated product was found in 350⁰C reaction. Furthermore, the conversion of guaiacol was improved when the hydrogen pressure was increased from 3bars to 6bars. In this case, higher hydrogen pressure did not alter the reaction direction or pathway as the product formed remains the same. Lastly, the possible reaction pathways of HDO of guaiacol was predicted to be a parallel reaction of transalkylation and demethoxylation. Transalkylation of guaiacol yields catechol and di-methoxybenzene while demethoxylation of guaiacol produces phenol and intermediate product, methanol